GENUS BERRIASELLA (AMMONOIDEA) AND AMMONOID ZONATION IN THE BERRIASIAN OF THE CRIMEAN MOUNTAINS - Arkad'ev V.V.; Bogdanova T.N. (My University, 2004)
Six Berriasella species (Ammonoidea) found in the Berriasian sediments of the Crimean Mountains are B. jacobi Maz., B. calisto (d'Orb.), B. subcalisto (Touc.), B. oppeli (Kil.), B. moesica Nik. et Man. and B. chomeracensis (Touc.), the last two being first encountered. Based on the recognized standard zones jacobi-occitanica-boissieri, the Berriasian of the Crimea is correlated with coeval sections in other Mediterranean areas. Systematic description is presented for all the species.
Keywords: Berriasian; Mesozoic::Cretaceous::Lower::Berriasian; Мезозой::Меловая::Нижний::Берриасский